Affordable car selection system using analytic network process (ACaSe) / Noorsyariena Izana Mohd Noorhanafi - Mohd Noorhanafi, Noorsyariena Izana (2014)
Decision-making is the normal part in our life and it can be made based on the experiences and knowledge. For the first time car buyer, making a decision on which car that need to be bought is not an easy task. Several car criteria need to be taken into consideration such as financial, performance, appearance, convenience and safety. Currently, there are no specific systems for the car buyers that able to assist them in making a wise decision in order to buy a new car. To overcome this problem an Affordable Car Selection System using Analytic Network Process (ACaSe) is developed to assist the user on selecting car criteria based on Analytic Network Process (ANP) technique. This system provides five types of car such as Perodua Myvi, Proton Suprima S, Honda City, Toyota Vios and Suzuki Swift which are suitable for the first time buyers’ selection (taking into consideration their income as new graduates). Users are able to select prioritization of their own car criteria based on the criteria provided by the system. The process in decision making is integrated with ANP technique. The evaluation part has been done with 40 respondents. There are five constructs has been evaluation; interface and design, navigation, functionality, content and booking process. Construct with the highest result is regarding the content with 60% respondents are strongly agree with it and mode for this construct is 5. The highest mean based on user feedback for this construct is item C02 (Mean = 4.6, SD = 0.516). This indicates that, the respondents are agreeing with the content in this system because the information provided in this system is helpful for them and user knows where to find the information needed.